2002
DOI: 10.1093/gerona/57.10.b359
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Strength as a Predictor of All-Cause Mortality in Healthy Men

Abstract: Low muscle strength is associated with mortality, presumably as a result of low muscle mass (sarcopenia) and physical inactivity. Grip strength was longitudinally collected in 1071 men over a 25-year period. Muscle mass was estimated by using 24-hour creatinine excretion and physical activity values, obtained by questionnaire. Survival analysis examined the impact of grip strength and rate of change in strength on all-cause mortality over 40 years. Lower and declining strength are associated with increased mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
508
1
42

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 734 publications
(568 citation statements)
references
References 26 publications
17
508
1
42
Order By: Relevance
“…Resulting height loss could affect normal functioning of the respiratory and gastrointestinal systems, (13) which in turn might lead to early satiety, poor nutritional status, and weight loss. (13) Height loss also appears to be related to sarcopenia, (32) which is defined as the loss of skeletal muscle mass and strength with aging and is associated with weight loss (40)(41)(42)(43) and increased mortality. (33)(34)(35) We found increased mortality associated with marked HL due to CHD or stroke and respiratory diseases, but no increased cancer mortality.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…Resulting height loss could affect normal functioning of the respiratory and gastrointestinal systems, (13) which in turn might lead to early satiety, poor nutritional status, and weight loss. (13) Height loss also appears to be related to sarcopenia, (32) which is defined as the loss of skeletal muscle mass and strength with aging and is associated with weight loss (40)(41)(42)(43) and increased mortality. (33)(34)(35) We found increased mortality associated with marked HL due to CHD or stroke and respiratory diseases, but no increased cancer mortality.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…Hand grip strength is a measurement of choice, known to be associated with muscular functioning in other muscle groups and with activities of daily living (Melzer et al 2007;Frederiksen et al 2002;Rantanen et al 2003). Previous research has shown that hand grip strength is a significant predictor of health status, postoperative recovery, recovery from injury, protein loss, cause-specific and total mortality (2000) a h 2 : heritability of biomarkers, both cross-sectional and of their change with age (Δ), if reported (Metter et al 2002), and disability (Frederiksen et al 2002;Rantanen et al 2003). Muscle mass and crosssectional area are highly heritable, ranging from 60% to 90% (Huygens et al 2004;Seeman et al 1996;Hsu et al 2005).…”
Section: Biomarkers Of Agingmentioning
confidence: 99%
“…2002). The rate of loss of muscle mass and function with aging is noted to differ between individuals, which gave rise to “usual” and “successful” aging hypothesis (Rowe and Kahn 1987).…”
Section: Introductionmentioning
confidence: 99%